Bureaucratic Behavior in the Implementation of Capital Expenditure Budget in the Office of Public Work and Spatial Planning of Sumedang Regency - Suparman, Nanang; Chandra, Deddi; Sari, Avid Leonardi (Jurnal Bina Praja, 2019)
The behavior of bureaucratic apparatus in the implementation of the capital expenditure budget in the Office of Public Works and Spatial Planning of Sumedang Regency, West Java Province, still shows a deviant tendency. The problem behind the bad behavior of bureaucratic apparatus in managing the state budget is because of the lack of self-control to prevent deviant behavior and, vice versa, there is a strong intention to behave deviant. Therefore, the purpose of this study is to examine the implementation of the capital expenditure budget in the perspective of the behavior of individual bureaucratic apparatus related to intentions that are formed from a combination of attitudes, subjective norms, and behavioral control. The research method used is qualitative with a behavioral approach so that it can explain the data and information obtained from observation, interviews, and focus group discussions. The validity and reliability of the research are explained and verified with the theories of public administration science so that answers can be formulated as the formulation of the problem. The results showed that the behavior of the bureaucratic apparatus was determined by the intention of a number of efforts and endeavors to make a growing deviation in the implementation of the capital expenditure budget, it was built from the attitude of bureaucratic apparatus that lacked integrity and ployed loyalty. The attitude of the apparatus is in line with the subjective norms of the leaders and stakeholders who hope that each individual who plays a role in project management will get a number of resources determined according to the budget ceiling amount of the contract package for construction work and procurement of operational goods. The attitude and subjective norms of the bureaucratic apparatus can be achieved well because the behavior control is confirmed to be very low.